Global Market Expansion And Strategies In Wireless Telecomunication Industry Case Study Of Vodafone Group PLC - Abdelelah Baasher, Mohamed Elfateh (2006)
This case study is discusses and evaluates about Vodafone Group PLC and its global expansion in the global wireless telecommunication service industry.Overall, the study intends to look at Vodafone\'s future expansion, growth and global strategies within the concept of globalization and competitive advantages issues.